Faktor-Faktor Yang Mempengaruhi Kepuasan Kerja Perawat Di Rumah Sakit Siti Rahmah Padang : Factors Affecting Job Satisfaction of Nurses at Siti Rahmah Padang Hospital - Dewi Murni; Sidaria; Annisa; Maharani (Fakultas Keperawatan Universitas Andalas, 2022)
Job satisfaction is an individual’s general attitude towards the work he does. Nurses’ job satisfaction will reflect the level where a nurse has responsibility and likes work. Selecting the work given or assigned will positively impact both the nurse herself and the patient. Job satisfaction is (job satisfaction) an affective or emotional response to various aspects of one's work. The factors that influence the job satisfaction of nurses are motivation, environment, and the role of the manager. This type of research is quantitative with a cross-sectional model approach. The population of this study was all nurses who served in the inpatient room of RSI Siti Rahmah Padang, with a total sample of 50 nurses. The sampling technique used is proportional stratified random sampling, which meets the sample criteria. Data was taken using a questionnaire containing the item, job satisfaction of nurses. The motivation variable is the dominant factor that affects the job satisfaction of nurses, with a value of = 0.007. It is hoped that the hospital will review the motivations that can increase the job satisfaction of nurses and the policies taken and make decisions.